Equal Protection of the Law: The Persons with Disabilities (Equal Opportunities) Act, 2014, Bahamas - Bain, Bernadette (International Journal of Bahamian Studies, 2016)
The Persons with Disabilities (Equal Opportunities) Act, 2014 is a new and informative piece of legislation, the purpose of which is to provide equal opportunities for persons with disabilities. This paper explores the basis of the Act, which has its foundation in the United Nations Convention on the Rights of Persons with Disabilities. The legislation further facilitates the rights and freedoms provided under the Bahamian Constitution, and underscores fundamental rights. This analysis of the Persons with Disabilities (Equal Opportunities) Act, 2014, examines the nature and scope of equal rights and whether the Act provides adequate enforcement. The aim of the provisions is to restrict discrimination against persons with disabilities by providing opportunities on an equal basis and to require persons having dealings with the disabled to accommodate their needs. It is questionable whether the Act fulfils its purpose and whether penalties for failure to comply with the Act are adequate, as there is a lacuna or gap in the law, which hinders purposeful rights.